The Influence of Work Discipline and Loyalty on Employee Performance at PT. Fajar Mandiri Barokah Sumedang Regency - Utomo, Sudibyo Budi (Institut Agama Islam Sunan Giri Ponorogo, 2022)
This research aims to determine the influence of discipline and work loyalty on employee performance at PT. Fajar Mandiri Barokah, partially and simultaneously. The research method used in this research is descriptive and verification with a quantitative approach. Descriptive analysis is used to describe respondents' responses regarding research variables. Meanwhile, verification analysis or hypothesis verification is whether there is an influence of discipline and work loyalty on employee performance. In this study, a saturated sample of 30 PT employees was taken. Fajar Mandiri Barokah Sumedang Regency. Data instrument testing was carried out using validity and reliability tests, while for verification analysis using a correlation test with the results of a simultaneous correlation between discipline and work loyalty on employee performance was 0.804 which means it has a very strong relationship, multiple linear regression analysis with the result Y = 4.910 + 0.367 x1 + 0.921 x2. a = 4.910 This shows that if the value of work discipline and loyalty is zero then the employee performance value is 4.910. b1 = 0.367 This shows that every 1% increase in work discipline will be followed by an increase in employee performance of 0.367. b2 = 0.921 This shows that every 1% increase in work loyalty will be followed by an increase in employee performance of 0.921. From the calculation of the coefficient of determination, discipline and work loyalty simultaneously have a strong influence on employee performance of 64.6%. Then, for the simultaneous F test, the decision making criteria were found to be that H1 was accepted because the value of Fcount > Ftable (24.645 > 3.35). It can be concluded that work discipline and loyalty influence employee performance at PT. Fajar Mandiri Barokah.